PENINGKATAN PRODUKSI DAN PENGEMBANGAN PEMASARAN INDUSTRI RUMAH TANGGA PANGAN KHAS KABUPATEN TABANAN IBU SUMAWATI - Made Agus Putra Subali; I Gusti Rai Agung Sugiartha; Anak Agung Gede Purantara (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
The partner traditional food home industry sells lawar, tum, and timbungan. Every day the partners process 6 kg of meat, 0.5 kg of chilies, 1 kg of shallots, and 0.5 kg of garlic. The amount of production in a day reaches 5 timbungan, 12 packs of lawar, and 50 packs of tum. The produce is marketed locally at partners' kiosks from four in the afternoon to seven in the evening. The partner's business has the potential to develop further, because the number of orders on holidays and weekends can increase by up to 50% currently, the partner has problems with a shortage of production and product marketing quantities. The solution to overcome partner problems is carried out by providing assistance with production equipment, installing packaging labels, and installing brochures, banners, and promotions via social media Instagram and Facebook. Based on the activities that have been carried out, the results obtained are that the production equipment assistance provided is able to increase the number of partners' production by up to 50% and make the production time process more efficient. Creating Instagram and Facebook social media can be an alternative for marketing partner products to reach a wider market share. Apart from that, other capabilities obtained by partners, such as the use of production equipment and product packaging with packaging labels, have increased by up to 100%.